Answer:
x-36=7
Step-by-step explanation:
x-36=7
x=36+7
x=43
( x-5)/-2=(x-1)/-3
Cross multiply
-3(x-5)=-2(x-1)
Distribute
-3x +15 = -2x +2
Add 2x to both sides
-x +15 = 2
Subtract 15 from both sides
-x = -13
x=13
The answer would be c)x+3 because if you substitute 1 for x, the expression would be 1+3 and it comes out as 4. Also, if you substitute 4 for x the expression would be 4+3 which comes out to 7
Hope this helps!
Answer:
combined properties
Step-by-step explanation:
Answer:
so Y= 150 + 50x
Step-by-step explanation:
so y = 150 + 50 x 2 will = 250
50 x 2 = 100
100 + 150Y
= 250